Excess 30-Day Heart Failure Readmissions and Mortality in Black Patients Increases With Neighborhood Deprivation. (December 2020) - Patel, Shivani A.; Krasnow, Maya; Long, Kaitlyn; Shirey, Theresa; Dickert, Neal; Morris, Alanna A.
Abstract : Background: Longstanding racial disparities in heart failure (HF) outcomes exist in the United States, in part, due to social determinants of health. We examined whether neighborhood environment modifies the disparity in 30-day HF readmissions and mortality between Black and White patients in the Southeastern United States. Methods: We created a geocoded retrospective cohort of patients hospitalized for acute HF within Emory Healthcare from 2010 to 2018. Quartiles of the Social Deprivation Index characterized neighborhood deprivation at the census tract level. We estimated the relative risk of 30-day readmission and 30-day mortality following an index hospitalization for acute HF. Excess readmissions and mortality were estimated as the absolute risk difference between Black and White patients within each Social Deprivation Index quartile, adjusted for geographic clustering, demographic, clinical, and hospital characteristics. Results: The cohort included 30 630 patients, mean age 66 years, 48% female, 53% Black. Compared with White patients, Black patients were more likely to reside in deprived census tracts and have higher comorbidity scores. From 2010 to 2018, 29.4% of Black and 23.0% of White patients experienced either a 30-day HF readmission or 30-day death ( P <0.001). Excess in composite 30-day HF readmissions and mortality for Black patients ranged from 3.9% (95% CI, 1.5%–6.3%; P =0.0002) to 6.8% (95% CI, 4.1%–9.5%; P <0.0001) across Social Deprivation Index quartiles. Accounting for traditional risk factors did not eliminate the Black excess in combined 30-day HF readmissions or mortality in any of the neighborhood quartiles. Conclusions: Excess 30-day HF readmissions and mortality are present among Black patients in every neighborhood strata and increase with progressive neighborhood socioeconomic deprivation. Abstract : Supplemental Digital Content is available in the text.